GCP16 stabilizes the DHHC9 subfamily of protein acyltransferases through a conserved C-terminal cysteine motif - Nguyen, Phillip L.; Greentree, Wendy K.; Kawate, Toshimitsu; Linder, Maurine E. (Frontiers in Physiology, 2023)
Protein S-acylation is a reversible lipid post-translational modification that allows dynamic regulation of processes such as protein stability, membrane association, and localization. Palmitoyltransferase ZDHHC9 (DHHC9) is one of the 23 human DHHC acyltransferases that catalyze protein S-acylation. Dysregulation of DHHC9 is associated with X-linked intellectual disability and increased epilepsy risk. Interestingly, activation of DHHC9 requires an accessory protein—GCP16. However, the exact role of GCP16 and the prevalence of a requirement for accessory proteins among other DHHC proteins remain unclear. Here, we report that one role of GCP16 is to stabilize DHHC9 by preventing its aggregation through formation of a protein complex. Using a combination of size-exclusion chromatography and palmitoyl acyltransferase assays, we demonstrate that only properly folded DHHC9-GCP16 complex is enzymatically active in vitro. Additionally, the ZDHHC9 mutations linked to X-linked intellectual disa-bility result in reduced protein stability and DHHC9-GCP16 complex formation. Notably, we discov-ered that the C-terminal cysteine motif (CCM) that is conserved among the DHHC9 subfamily (DHHC14, -18, -5, and -8) is required for DHHC9 and GCP16 complex formation and activity in vitro. Co-expression of GCP16 with DHHCs containing the CCM improves DHHC protein stability. Like DHHC9, DHHC14 and DHHC18 require GCP16 for their enzymatic activity. Furthermore, GOLGA7B, an accessory protein with 75% sequence identity to GCP16, improves protein stability of DHHC5 and DHHC8, but not the other members of the DHHC9 subfamily, suggesting selectivity in accessory protein interactions. Our study supports a broader role for GCP16 and GOLGA7B in the function of human DHHCs.